2017
DOI: 10.1038/s41598-017-13623-6
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin G20210A (rs1799963) polymorphism increases myocardial infarction risk in an age-related manner: A systematic review and meta-analysis

Abstract: G20210A polymorphism (rs1799963) within the prothrombin gene is associated with a higher circulation level of prothrombin, thus increasing the likelihood of developing myocardial infarction (MI). Opinions differ regarding the correlation between prothrombin G20210A genotype and MI risk, which prompted us to conduct a meta-analysis to determine this association. PubMed, EMBASE, Web of Science and CNKI were searched for pertinent reports. A total of 34 studies involving 14 611 MI cases and 84 358 controls were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
(65 reference statements)
1
16
0
4
Order By: Relevance
“…39,40,53 A study by Ye at al, 43 including 8211 cases and 12 356 controls, confirmed that the presence of FII20210A represents a significant, but small risk for MI (OR, 1.25; 95% CI, 1.05-1.50). A more recent report by Li et al 54 (including a total of 33 studies with 13 488 cases and 77 085 controls) showed a similar, significant association between FII20210A and MI in the allele model (A vs G; OR, 1.43; 95% CI, 1.18-1.72) with almost identical results in the heterozygote (GA vs GG) or dominant model (GA+AA vs GG) as well. In this study, authors have performed subgroup analyses and found that the association remained significant in those of Caucasian origin.…”
mentioning
confidence: 61%
“…39,40,53 A study by Ye at al, 43 including 8211 cases and 12 356 controls, confirmed that the presence of FII20210A represents a significant, but small risk for MI (OR, 1.25; 95% CI, 1.05-1.50). A more recent report by Li et al 54 (including a total of 33 studies with 13 488 cases and 77 085 controls) showed a similar, significant association between FII20210A and MI in the allele model (A vs G; OR, 1.43; 95% CI, 1.18-1.72) with almost identical results in the heterozygote (GA vs GG) or dominant model (GA+AA vs GG) as well. In this study, authors have performed subgroup analyses and found that the association remained significant in those of Caucasian origin.…”
mentioning
confidence: 61%
“…Besides isolated Lp(a)-hyperlipoproteinaemia, our patient carries the prothrombin rs1799963 genetic variant associated with an increased risk of venous thromboembolism as well as with an increased overall risk of MI, an association markedly increased in young individuals and for which antiplatelet therapies seem to be the adequate treatment 3 …”
Section: Discussionmentioning
confidence: 89%
“…Lipoprotein (a) levels above 75 nmol/L (30 mg/dL) are considered pro-atherothrombotic and are found in 20% of the population 2 . Here, we report a young patient with severe recurrent episodes of coronary syndromes presenting with very-high circulating Lp(a) levels and the prothrombin rs1799963 (G20210A) genetic variant associated with an increased risk of thromboembolism 3 …”
Section: Introductionmentioning
confidence: 93%
“…Однако эта связь отсутствовала у больных старше 55 лет [30]. Доминирующая роль приобретенных факторов риска при ИМ, таких как дислипидемия, курение, ослабляла влияние генетического фактора у пожилых людей [37]. В проведенном нами иссле-довании полиморфизм гена G20210A регистрировался лишь в 1 (0,25 %) случае и не ассоциировался с увеличением риска развития ОИМ, что подтверждает результаты небольшого пилотного исследования, в котором больные с ОИМ при НАКА и стенозирующем атеросклерозе КА существенно не различались по частоте носительства неблагоприятных генотипов генов системы гемостаза [5].…”
Section: нака -невыраженный атеросклероз коронарных артерийunclassified